Artificial intelligence in asset management companies - an exploratory study in business practice - Mencke, Eric (2024)
This research explores the role of AI in key account management (KAM) within asset management companies. Through seven semi-structured expert interviews, key tasks, success factors, and challenges of KAM are identified, alongside current AI usage, its impact, and future organizational plans. Findings reveal minimal current AI implementation, focusing on administrative tasks, with significant potential in reporting and communication. Challenges include data sensitivity, regulatory constraints, and high implementation costs. Recommendations highlight the need for targeted training, use-case-based AI integration, and enhanced change management strategies. The study addresses a literature gap, providing insights for academia and practical implications for asset management firms.